Effort to Improve Work Motivation at State Owned Corporations Based on Leadership Style, Human Resources Training and Promotion Policies - Misbahuddin Azzuhri (Jurnal Aplikasi Manajemen, 2012)
Work motivation is an important factor for the organization to achieve its goal. Various efforts are carryout by an organization to improve the staff motivation. Thos efforts were implemented by human resources (HR) training and promotion policy. Realizing that leadership style and promotion policy are the key elements of human resource management. This research considers that it is important to analyze the work motivation both directly or indirectly. According to the background and the statement of the problem, the aim of the research is to analyze the effect of the leadership style, HR training, and promotion policy on work motivation which consist of intrinsic and extrinsic motivation. The research was an analytic design cross sectional study which the population of the research was all staffs of PT Pertamina (Persero) Surabaya Regional Office with 70 officials. The questionnaire was used to collect data. The measurement of the variables was described in the statement form of items with interval scale as the reference. The score shift is 1-5. the variable used are leadership style, HR training, promotion policy, and work motivation. Moreover, the research results suggested that there is no direct effect of leadership style on work motivation, but it has indirect effect on work motivation through promotion.Keywords: leadership style, HR training, promotion policy, work motivation